6x-3-(5-x)(2x-1)=0

Simple and best practice solution for 6x-3-(5-x)(2x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3-(5-x)(2x-1)=0 equation:


Simplifying
6x + -3 + -1(5 + -1x)(2x + -1) = 0

Reorder the terms:
6x + -3 + -1(5 + -1x)(-1 + 2x) = 0

Multiply (5 + -1x) * (-1 + 2x)
6x + -3 + -1(5(-1 + 2x) + -1x * (-1 + 2x)) = 0
6x + -3 + -1((-1 * 5 + 2x * 5) + -1x * (-1 + 2x)) = 0
6x + -3 + -1((-5 + 10x) + -1x * (-1 + 2x)) = 0
6x + -3 + -1(-5 + 10x + (-1 * -1x + 2x * -1x)) = 0
6x + -3 + -1(-5 + 10x + (1x + -2x2)) = 0

Combine like terms: 10x + 1x = 11x
6x + -3 + -1(-5 + 11x + -2x2) = 0
6x + -3 + (-5 * -1 + 11x * -1 + -2x2 * -1) = 0
6x + -3 + (5 + -11x + 2x2) = 0

Reorder the terms:
-3 + 5 + 6x + -11x + 2x2 = 0

Combine like terms: -3 + 5 = 2
2 + 6x + -11x + 2x2 = 0

Combine like terms: 6x + -11x = -5x
2 + -5x + 2x2 = 0

Solving
2 + -5x + 2x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(1 + -2x)(2 + -1x) = 0

Subproblem 1

Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5

Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Solution

x = {0.5, 2}

See similar equations:

| 32=q/2 | | 8x-22=-5(x-6) | | x*15-180=x*6-9 | | 3(v+1)=-2v-32 | | -3t(2t-5)+4t=5t-9 | | 2x(x+1)-(x+1)=0 | | -.02k+1=11 | | 12s=89 | | 6+49x=21x+42 | | 2x+(x+12)=180 | | .02k+1=11 | | 9(x-2)=3(x-2) | | 4.5x-39=2.2x+7 | | n+n+m=2 | | -3t(4t-4)+8t=3t-4 | | 7x+4=x+10 | | x=y/6(16-z) | | -27x^2+48x-5= | | 4(t-3)=2t+7 | | -2(3t-4)+3t=2t-3 | | -27x^3+48x-5= | | 10x^2+2.5x-45=0 | | 3x+11=6x-4 | | 5+6=5+x | | 6x^2-4x=-11 | | 8+y=6+2y | | -5(3t-2)+2t=4t-9 | | x^4-8x^3+98x^2-648x+1377=0 | | 36m^-4n^-6/4mn^-2p^-4 | | -x^2-100=0 | | 19=4-2m-m+7 | | (2x+4)+(3x-13)=180 |

Equations solver categories